The use of a Rotary Asphalt Broom to Groom Aggregate Forest Roads - Ben Leshchinsky; Erica Kemp; Robin Wortman; Kevin Boston (Croatian Journal of Forest Engineering, 2017)
Due to the dispersed nature of forestry operations in much of the world, only a subset of a given forest road network are used in any year. Specifically, spur roads are generally only used when harvesting operations are adjacent to roadways; otherwise, they remain unused or only have infrequent administrative traffic. During these periods of light use, a substantial amount of organic litter may build up on the roads. As this detritus accumulates and decays, it creates conditions that encourage the growth of unwanted vegetation in the roadway, accelerating the contamination of the surface aggregate. This organic material can degrade the road by retaining moisture and creating a less tractive road surface. Contemporary forest practices control this unwanted vegetation by using a combination of grading or herbicides, at significant expense. One potential alternative treatment is the utilization of a rotary-mounted asphalt broom for vegetation and debris removal. A series of field trials were performed on wet, contaminated forest roads, in which we evaluated vegetation, debris removal effectiveness, and tire slip on segments of road before and after sweeping. The combined effects of wire and synthetic bristles on the rotary broom proved effective in both increasing traction and removing unwanted debris and vegetation from the road surface. Application of this technique was expedient, and did not result in significant loss of surface aggregate, removing on average less than 1% of the aggregate surface.